Performance of Ceriporiopsis sp. in the Treatment of Black Liquor Wastewater - Sari, Ajeng Arum (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2016)
High amounts of black liquor wastewater are generated from bioethanol production by using oil palm empty fruit bunches. It contains an alkaline solution (NaOH), so it is quite toxic for aquatic ecosystems if discharged directly into waters. Black liquor has been treated by coagulation method, and it still needs additional treatment. This study aimed to determine degradation of black liquor wastewater by selected white-rot fungi (WRF). Five different strains of WRF have been tested for their ability to decolorize black liquor on agar and liquid media. Out of five fungi studied, two fungi, Ceriporiopsis sp. and Phanerochaete chrysosporium, showed the capacity to grow more than 50% on agar medium. In liquid medium, the percentage of decolorization of 15,000 ppm coagulated and diluted black liquor ranged from 70 to 89% at 30 days depending on the fungal strain. Ceriporiopsis sp. showed the better ability to decolorize black liquor than P. chrysosporium. The performance of Ceriporiopsis sp was evaluated regarding decolorization of black liquor, chemical oxygen demand (COD), and mycelial dry weight both in coagulated black liquor and original black liquor. The color of original and coagulated black liquor can be decolorized up to 90.13 and 86.85%, respectively. COD in original and coagulated black liquor was reduced up to 70.17 and 40.09%, respectively. The presence of coagulant Poly Aluminum Chloride (PAC) inhibited degradation of black liquor by fungus. The result demonstrated that Ceriporiopsis sp has a potential alternative to treat black liquor wastewater.Ã‚Â